2020
DOI: 10.1186/s12974-020-01998-9
|View full text |Cite
|
Sign up to set email alerts
|

The peri-menopause in a woman’s life: a systemic inflammatory phase that enables later neurodegenerative disease

Abstract: The peri-menopause or menopausal transition—the time period that surrounds the final years of a woman’s reproductive life—is associated with profound reproductive and hormonal changes in a woman’s body and exponentially increases a woman’s risk of cerebral ischemia and Alzheimer’s disease. Although our understanding of the exact timeline or definition of peri-menopause is limited, it is clear that there are two stages to the peri-menopause. These are the early menopausal transition, where menstrual cycles are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(69 citation statements)
references
References 185 publications
(237 reference statements)
1
68
0
Order By: Relevance
“…Moreover, increasing evidence suggests that gonadal hormones act as neurosteroids that are produced in the brain and, thus, rapidly alter cognition and other neural functions [4]. Therefore, the decrease induced in estrogen levels by menopause or ovariectomy may not only increase the incidence of inflammatory pathologies, but also decrease neurogenesis and neuronal plasticity [5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, increasing evidence suggests that gonadal hormones act as neurosteroids that are produced in the brain and, thus, rapidly alter cognition and other neural functions [4]. Therefore, the decrease induced in estrogen levels by menopause or ovariectomy may not only increase the incidence of inflammatory pathologies, but also decrease neurogenesis and neuronal plasticity [5].…”
Section: Introductionmentioning
confidence: 99%
“…The content validity showed that the CVI ranged from 0.82 to 1.00 for consistency, representativeness, relevance, and clarity of each construct, resulting in 25 items for the P-MFSMS. Perimenopause and menopause were based on the classification of the American Society for Reproductive Medicine’s Stages of Reproductive Aging Workshop (STRAW), which separates a woman’s life into seven segments, including segments −2, −1, and 0, ranging from the onset of menstrual cycles at menarche and the reproductive age to the peri-menopausal and postmenopausal phases [ 21 , 22 , 23 ]. In order to elucidate this distribution, women with regular menstrual bleeding during the last year were classified as premenopause; those with irregular bleeding during the last 12 months or with an age accompanied by less than one-year natural amenorrhea were defined as perimenopause; and the age at natural menopause was used to indicate the timing of menopause, which was confirmed after one year of amenorrhea [ 21 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Perimenopause and menopause were based on the classification of the American Society for Reproductive Medicine’s Stages of Reproductive Aging Workshop (STRAW), which separates a woman’s life into seven segments, including segments −2, −1, and 0, ranging from the onset of menstrual cycles at menarche and the reproductive age to the peri-menopausal and postmenopausal phases [ 21 , 22 , 23 ]. In order to elucidate this distribution, women with regular menstrual bleeding during the last year were classified as premenopause; those with irregular bleeding during the last 12 months or with an age accompanied by less than one-year natural amenorrhea were defined as perimenopause; and the age at natural menopause was used to indicate the timing of menopause, which was confirmed after one year of amenorrhea [ 21 , 23 ]. Regular exercise was defined as either three or more sessions per week, for at least 20 min per session, of jogging–running, hiking, biking, swimming, or dancing resulting in a medium-to-large increase in reported heart rate or five or more sessions per week, for at least 30 min per session, of any physical activity, such as walking, gardening or yard work, or calisthenics, that resulted in at least some increase in reported heart rate [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ER- α acts as a neuroprotective element against AD by maintaining intracellular signaling cascades [ 111 ]. ER- β is a potent regulator of the innate immune response as well as is involved in the regulation of neuronal mitochondrial function [ 112 ]. Besides, reduced expression of ER- α has been found in hippocampal neurons of AD subjects.…”
Section: Hormone Replacement Therapymentioning
confidence: 99%